Leukocyte function assessed via serial microlitre sampling of peripheral blood from sepsis patients correlates with disease severity - Jundi, Bakr; Ryu, Hyunryul; Lee, Do-Hyun; Abdulnour, Raja-Elie E.; Engstrom, Braden D.; Duvall, Melody G.; Higuera, Angelica; Pinilla-Vera, Mayra; Benson, Maura E.; Lee, Jaemyon; Krishnamoorthy, Nandini; Baron, Rebecca M.; et al. (Nature biomedical engineering, 2019)
Dysregulated leukocyte responses underlie the pathobiology of sepsis, which is a leading cause of death. However, measures of leukocyte function are not routinely available in clinical care. Here we report the development and testing of an inertial microfluidic system for the label-free isolation and downstream functional assessment of leukocytes from 50 μl of peripheral blood. We used the system to assess leukocyte phenotype and function in serial samples from 18 hospitalized patients with sepsis and 10 healthy subjects. The sepsis samples had significantly higher levels of CD16 dim and CD16 − neutrophils and CD16 + ‘intermediate’ monocytes, as well as significantly lower levels of neutrophil-elastase release, O 2 − production and phagolysosome formation. Repeated sampling of sepsis patients over 7 days showed that leukocyte activation (measured by isodielectric separation) and leukocyte phenotype and function were significantly more predictive of the clinical course than complete-blood-count parameters. We conclude that the serial assessment of leukocyte function in microlitre blood volumes is feasible and that it provides significantly more prognostic information than leukocyte counting. The serial assessment of the functional parameters of leukocytes isolated via an inertial microfluidic system from 50 μl of peripheral blood from sepsis patients provides significantly more prognostic information than leukocyte counting.